Microwave pyrolysis of oily sludge for potential synthesis gas (syngas) production - Mokhtar, Nur Mustika (2011)
Abundant amount of oily sludge generated from petroleum refinery wastewater treatment plant is becoming a serious problem in our country due to the high production of petroleum usable products. The toxicity of the sludge is the major obstacle to treat this waste using conventional method such as landfarming and incineration due to the adverse environmental impacts and human health. The success of thermal treatment on others biomass to produce gas, char and bio-oil inspired this study to assess the possibility of oily sludge to be pyrolyzed in a modified microwave oven targeting at high synthesis gas (syngas) production. The oily sludge was taken from a local petroleum refinery plant and placed directly into a fixed-bed quartz reactor fixed in a modified microwave. Microwave absorbers were added to raise the temperature during for pyrolysis reaction. The effect of four parameters on products yield were investigated including microwave absorbers addition and composition, sweep gas flow rate and initial moisture content. In summary, microwave energy can successfully pyrolyze untreated oily sludge with addition of 10% of CAC as absorber using nitrogen gas at flow rate of 200 mL/min to produce medium-amount gas and high volume reduction of 93% for lower cost disposal. Besides, this method was proven to save time as only 30 minutes was need for both drying and pyrolysis with no pre-treatment is needed prior to the pyrolysis treatment. The produced gas concentration of H2 (15%) and CO (13.3%) giving lower heating value (LHV) at 5.57 MJ/m3 in this study. The calorific value of the char is 7.03 MJ/kg which is higher than that of the sewage sludge char, but still low to be used as biofuel. The relatively large pore volume in the mesoporous range is expected to have low adsorption capacity. Monoaromatic compounds dominate the bio-oils for those without absorber and added with 10% of CAC although low polycyclic aromatic hydrocarbon (PAH) was noticed in the pyrolytic bio-oils